Novel low-temperature synthesis of nanosized NiZn ferrite - Verma, S.; Pradhan, S. D.; Pasricha, R.; Sainkar, S. R.; Joy, Pattayil Alias (Journal of the American Ceramic Society, 2005)
Nanosized NiZn ferrite powder is synthesized by a low-temperature method, using a unique combination of citric acid and glycine. An appropriate molar ratio of both citric acid and glycine offers a low-temperature synthetic route by incorporating the complexation behavior of citric acid and the combustion nature of glycine. Thermal decomposition/controlled autocatalytic combustion of the composite gel occurs at a low temperature of around 175 degrees C, with the evolution of a large amount of gases. Transmission electron microscopic studies showed that the average particle size of the ferrite obtained is similar to 2.5 nm, with a narrow size distribution. Uniformly distributed fine-grained microstructure with low porosity is obtained for a sample sintered at 1000 degrees C.